FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KB IMPLANT DI PUSKESMAS SEBOROKRAPYAK KECAMATAN BANYUURIP KABUPATEN PURWOREJO - Sholichah, Nur; Lathifah, Ummi (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2022)
The major problem faced of Indonesia is the high rate population growth. Which the users of Long-Term Contraception Method specially Implan including to low. But it different with the results of the preliminary study in Puskesmas Seborokrapyak there is 269 IMPLAN Family Planning acceptors. Research Objectives is to know an overview of factors influencing the choosen of IMPLAN as Family Planning in the Seborokrapyak Community Health Center. Research Metodhology of this research is retrospektif survey with case control survey. Population in this research is all of fertile age women in the Seborokrapyak Community Health Center on September 2020-September 2021. Taking the sample are using random sampling technique. Research time in march-april 2022. Analysis Technique is Chi-Square. The result of this research showed that result of Chi-Square analysis got (p value=0.436) in occupation that means P value > 0,05 so there is no relationship between occupation and in parity the value is 0.035 it means <0,05 which There is relationship between parity with choosen of IMPLAN as Family Planning and with age got the value=0.028 it means There is relationship between age with choosen of IMPLAN as Family Planning.